(untitled) (Colombia Medica, 2016)
Background:An accurate understanding of co-occurrence and comorbidity of alcohol use disorders (AUD) in Colombia is crucial for public health. Objective:A secondary analysis was conducted, using a 2003/2004 government´s population database to determine the lifetime associations between AUD and other mental and addictive disorders in people of Colombia aged 18-65 years. Methods:Several statistical analysis were performed: testing prevalence difference in mental disorders by whether the individual had an AUD; a stratified analysis by gender and logistic regression analyses accounting for differences in demographic, socio-economic, behavioral and self-reported health status variables. Results:People with AUD comprised 9% of the population, of which 88% were males and on average 37 years old. They were more likely to be males, be working, and be current smokers; and less likely to be at home or retired. The population with AUD had greater chance to comply with criteria for all disorders but minor depressive disorder, post-traumatic stress disorder, nicotine dependence, and oppositional defiant disorder. Conclusion:This study demonstrates a high prevalence of mental disorders in the adult population with AUD in Colombia. The findings highlight the importance of comorbidity as a sign of disease severity and impact on public health and supports the need for training of more professionals and developing appropriate interventions and services.